2014
DOI: 10.1016/j.mayocp.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan, Other Antihypertensives, and Chronic Diarrhea Among Patients Undergoing Endoscopic Procedures: A Case-Control Study

Abstract: Objective To investigate a recent association between use of the angiotensin receptor-blocker (ARB) olmesartan and a severe enteropathy resembling celiac disease. Patients and Methods We searched our endoscopy database for all outpatient esophagogastroduodenoscopy (EGD) or colonoscopy examinations in patients at least 50 years of age during the dates January 1, 2007 to March 31, 2013. Cases were those whose examination indication was diarrhea, and controls were those whose examination indication was esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 7 publications
0
19
1
Order By: Relevance
“…In July 2013, FDA issued a warning that olmesartan may cause sprue-like enteropathy but this warning was later removed from the label of the drug (110). A case control study published recently (111) showed no statistically significant association between olmesartan and diarrhea among patients undergoing upper endoscopy (OR 1.99; 95% CI, 0.79–5.00) and colonoscopy (OR 0.63; 95% CI 0.23–1.74).…”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 92%
“…In July 2013, FDA issued a warning that olmesartan may cause sprue-like enteropathy but this warning was later removed from the label of the drug (110). A case control study published recently (111) showed no statistically significant association between olmesartan and diarrhea among patients undergoing upper endoscopy (OR 1.99; 95% CI, 0.79–5.00) and colonoscopy (OR 0.63; 95% CI 0.23–1.74).…”
Section: Safety and Tolerability Of Arbs In Hypertensionmentioning
confidence: 92%
“…Menne and Haller analyzed data collected in the ROADMAP study in which diabetic patients had received either 40 mg/d olmesartan (n ¼ 2232) or placebo (n ¼ 2215), and they found no differences in the occurrence of diarrhea or abdominal discomfort between these two groups. 22 In the retrospective case-control study by Greywoode et al, 23 analysis of clinical data from patients 50 years and older who had undergone esophagogastroduodenoscopy (n ¼ 2088) or colonoscopy (n ¼ 12 428) procedures found no significant association between olmesartan use and diarrhea. They also found no significant association between olmesartan use and histologic diagnosis of celiac disease or microscopic colitis.…”
Section: Diagnosis Treatment and Outcomementioning
confidence: 98%
“…They also found no significant association between olmesartan use and histologic diagnosis of celiac disease or microscopic colitis. 23 The study was limited, however, by the small number of patients taking olmesartan: 22 patients (1%) in the esophagogastroduodenoscopy group and 83 patients (0.7%) in the colonoscopy group.…”
Section: Diagnosis Treatment and Outcomementioning
confidence: 99%
“…positive celiac disease serology and/or a symptomatic improvement on a gluten free diet. Although questioned by some, 6,7 a number of case series 8,9 and one national case finding study 10 have since then reported additional cases of olmesartan-associated sprue-like enteropathy. Some data have also suggested that other ARBs, besides olmesartan, may induce similar outcomes.…”
Section: Introductionmentioning
confidence: 99%